Expanded North Pacific Subtropical Gyre and Heterodyne Expression During the Mid-Pleistocene - Taylor, S. P.; Patterson, M. O.; Lam, A. R.; Jones, H.; Woodard, S. C.; Habicht, M. H.; Thomas, E. K.; Grant, G. R. (Springer, 2022)
The Kuroshio Current (KC) and Kuroshio Current Extension (KCE) form a western boundary current as part of the North Pacific Subtropical Gyre. This current plays an important role in regulating weather and climate dynamics in the Northern Hemisphere in part by controlling the delivery of moisture to the lower atmosphere. Previous studies indicate the KCE responded dynamically across glacial and interglacial periods throughout the Pliocene-Pleistocene. However, the response of the KCE during Pleistocene super-interglacials has not been examined in detail. We present a ∼2.2 Ma record of X-ray fluorescence elemental data from Ocean Drilling Program Hole 1207A and employ hierarchical clustering techniques to demonstrate paleoenvironmental changes around the KCE. Time-frequency analysis identifies significant heterodyne frequencies, which suggests there were nonlinear interactions between high-latitude and low-latitude climate regulating expansion and contraction of the North Pacific Subtropical Gyre prior to the onset of the Mid-Pleistocene Climate Transition (MPT). We observe two periods of elevated ln Ca/Ti, which may represent sustained warmth with northward migrations of the KCE in the northwestern Pacific. These intervals correspond to Marine Isotope Stages 29-25, 15, and 11-9 and occur around recent climatic transitions, the MPT and Mid-Brunhes Event. Northward expansion of the subtropical gyre during these exceptionally warm interglacials would have delivered more heat and moisture to the high latitudes of the northwest Pacific. Furthermore, enhanced evaporation from the warm KCE vented to the lower atmosphere may have preconditioned the Northern Hemisphere for ice volume growth during two of the most recent periods of climate transition.Key PointsNonlinear influences on northwest Pacific oceanic circulation during the 41-kyr worldPronounced periods of warmth during MIS 29-25, 15, 11-9 under a colder climate regimeChanges in North Pacific Subtropical Gyre correspond to extreme Arctic warming events Peer ...